Pengaruh Distribusi dan Kualitas Produk Terhadap Kepuasan Pelanggan Studi Kasus Produk Air Minum pada PDAM Tirta Pakuan Kota Bogor - Sulistiono, Angga; Sylvianica, Yuniany (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2009)
This research was done to find out how product quality yielded By the company and the influence of the distribution and quality of product towards customers satisfaction will be. The research was carried out at drinking water of PDAM Tirta Pakuan Kota Bogor. The result of double regression analysis ia Y = 6,52 + 0,62 X 1 + (-0,14) X 2. It means that if disrtibution grade (X1) rises 1, then customers will increas 62 percent and if product quality grade (X2) rises 1, then customers satisfaction will decrease 14 percent. This equation functions to predict if distribution variable and product quality become different or change, then customers satisfaction variable changes as well. The result of double correlation coefficient is grade r = 0,66. It means that there is positive and significant influence of the distribution and quality of product towards customers satisfaction. The resul of double determination coefficient shows that the distribution and quality pf product contributes 44 percent in creating customers satisfaction. Key words: Distribution; Product quality; Customers satisfaction